How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M M; Pereira, J S; MAROCO, J; RODRIGUES, M L; RICARDO, C P P; OSÓRIO, M L; CARVALHO, I; Faria, T; PINHEIRO, C (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle